Making a viable city - Nuikina, Elena Vladimirovna (2014)
Functioning, sustainable and efficient development of urban areas is the principal goal of urban planners, decision-makers and urban economists worldwide. Social characteristics and economic factors that contribute to the well-being of inhabitants are the two explanations of local success. Taking one step farther, this dissertation explores how situatedness of a settlement in the extra-local economic networks and power relations shapes strategies, practices of and views on the city development. The theoretical contribution of the present work to the urban geography is the application of the concept of city viability in conjunction with the concepts of positionality and path dependence to improve our understanding of how the notion city viability is constructed, perceived and implemented in general. The search for sustainable scenarios is especially pressing among remote industrial localities of the regions of the Russian Far North. The majority of these settlements were established through a Soviet planning effort, specifically in order to provide extractive industries with manpower resources. Economic and political dependence on core regions, mono-profiled economic basis, reliance on resource extraction and geographic remoteness from the markers results in a limited spectrum of available livelihoods. An example of a settlement experiencing these challenges is the city of Vorkuta – the case study in this dissertation. The results from extensive fieldwork in Vorkuta bring new insights to the theoretical discussion on city viability in post-Soviet conditions. I show how dominant approaches to creating a viable city have transformed over time by looking at the city’s evolution from a GULAG camp to a modern community. It is sometimes claimed that new Soviet towns cannot be livable due to their misallocation, history of forced settlement and incredibly high maintenance costs (Pivovarov 1995; Pivovarov 2002; Hill and Gaddy 2003; Hill 2004). In this context, the dissertation demonstrates how these localities developed into places for permanent habitation and what principles and practices allowed them to persist during the reforms of the early 1990s. Soviet principles that underpin city viability were revisited, which resulted in the cost-efficiency approach to the local development and programs aimed at socio-economic, demographic and spatial restructuring of the northern periphery. Recent interest in the Arctic region has given rise to new ideas and practices to link northern communities to the markets and federal funding. Empirical findings from Vorkuta show how seemingly incompatible strategies and visions simultaneously co-exist and are used as cards of different suits in the play for a better future. This dissertation brings the voices of different actors and examines their contribution to the city- making process throughout three different historical periods. It is evident that the prospects of northern localities are to a great extent influenced by the socio-economic settings and practices inherited over time. Although path dependence imposes some limitations on the city development and leads to negative restrictions in some spheres, continuing legacies also provide potential for community well-being. Based on the example of Vorkuta, this work shows that path dependences can be utilised as a resource used for manipulation of remaining economic networks and power relations. Moreover, prosperity of the place is not merely a product of local forces, but is shaped by its position within extra-local political and economic relations and the ability of a city to reposition itself in a new situation. Functioning, sustainable and efficient development of urban areas is the principal goal of urban planners, decision-makers and urban economists worldwide. Social characteristics and economic factors that contribute to the well-being of inhabitants are the two explanations of local success. Taking one step farther, this dissertation explores how situatedness of a settlement in the extra-local economic networks and power relations shapes strategies, practices of and views on the city development. The theoretical contribution of the present work to the urban geography is the application of the concept of city viability in conjunction with the concepts of positionality and path dependence to improve our understanding of how the notion city viability is constructed, perceived and implemented in general. The search for sustainable scenarios is especially pressing among remote industrial localities of the regions of the Russian Far North. The majority of these settlements were established through a Soviet planning effort, specifically in order to provide extractive industries with manpower resources. Economic and political dependence on core regions, mono-profiled economic basis, reliance on resource extraction and geographic remoteness from the markers results in a limited spectrum of available livelihoods. An example of a settlement experiencing these challenges is the city of Vorkuta – the case study in this dissertation. The results from extensive fieldwork in Vorkuta bring new insights to the theoretical discussion on city viability in post-Soviet conditions. I show how dominant approaches to creating a viable city have transformed over time by looking at the city’s evolution from a GULAG camp to a modern community. It is sometimes claimed that new Soviet towns cannot be livable due to their misallocation, history of forced settlement and incredibly high maintenance costs (Pivovarov 1995; Pivovarov 2002; Hill and Gaddy 2003; Hill 2004). In this context, the dissertation demonstrates how these localities developed into places for permanent habitation and what principles and practices allowed them to persist during the reforms of the early 1990s. Soviet principles that underpin city viability were revisited, which resulted in the cost-efficiency approach to the local development and programs aimed at socio-economic, demographic and spatial restructuring of the northern periphery. Recent interest in the Arctic region has given rise to new ideas and practices to link northern communities to the markets and federal funding. Empirical findings from Vorkuta show how seemingly incompatible strategies and visions simultaneously co-exist and are used as cards of different suits in the play for a better future. This dissertation brings the voices of different actors and examines their contribution to the city- making process throughout three different historical periods. It is evident that the prospects of northern localities are to a great extent influenced by the socio-economic settings and practices inherited over time. Although path dependence imposes some limitations on the city development and leads to negative restrictions in some spheres, continuing legacies also provide potential for community well-being. Based on the example of Vorkuta, this work shows that path dependences can be utilised as a resource used for manipulation of remaining economic networks and power relations. Moreover, prosperity of the place is not merely a product of local forces, but is shaped by its position within extra-local political and economic relations and the ability of a city to reposition itself in a new situation.